Health literacy in a community with low levels of education: findings from Chakaria, a rural area of Bangladesh - Susmita Das; Mohammad Nahid Mia; Syed Manzoor Ahmed Hanifi; Shahidul Hoque; Abbas Bhuiya (BMC, 2017)
Abstract Background Health literacy (HL) helps individuals to make effective use of available health services. In low-income countries such as Bangladesh, the less than optimum use of services could be due to low levels of HL. Bangladesh's health service delivery is pluralistic with a mix of public, private and informally trained healthcare providers. Emphasis on HL has been inadequate. Thus, it is important to assess the levels of HL and service utilization patterns. The findings from this study aim to bridge the knowledge gap. Materials and Methods The data for this study came from a cross-sectional survey carried out in September 2014, in Chakaria, a rural area in Bangladesh. A total of 1500 respondents were randomly selected from the population of 80,000 living in the Chakaria study area of icddr, b (International Centre for Diarrhoeal Disease Research, Bangladesh). HL was assessed in terms of knowledge of existing health facilities and sources of information on health care, immunization, diabetes and hypertension. Descriptive and cross-tabular analyses were carried out. Results Chambers of the rural practitioners of allopathic medicine, commonly known as 'village doctors', were mentioned by 86% of the respondents as a known health service facility in their area, followed by two public sector community clinics (54.6%) and Union Health and Family Welfare Centres (28.6%). Major sources of information on childhood immunization were government health workers. Almost all of the respondents had heard about diabetes and hypertension (97.4% and 95.4%, respectively). The top three sources of information for diabetes were neighbours (85.7%), followed by relatives (27.9%) and MBBS (Bachelor of Medicine and Bachelor of Surgery) doctors (20.4%). For hypertension, the sources were neighbours (78.0%), followed by village doctors (38.2%), MBBS doctors (23.2%) and relatives (15%). The proportions of respondents who knew diabetes and hypertension control measures were 40.9% and 28.0%, respectively. More females knew about the control of diabetes (44.4% to 36.6%) and hypertension (31.1% to 24.2%) than males. Conclusions A low level of HL in terms of modern health service facilities, diabetes and hypertension clearly indicated the need for a systematic HL programme. The relatively high levels of literacy concerning immunization show that it is possible to enhance HL in areas with low levels of education through systematic awareness-raising programmes, which could result in higher service coverage.